2003
DOI: 10.1034/j.1600-0463.2003.t01-1-1110204.x
|View full text |Cite
|
Sign up to set email alerts
|

Routine genotyping of human papillomavirus samples in Denmark

Abstract: In order to examine a sensitive unbiased consensus PCR with routine sequencing for HPV typing, we analysed Danish male and female patients suspected of having an HPV infection. We used the well-characterised nested PCR setting with MY09/MY11 and GP5+/GP6+ primers, followed by routine cycle sequencing. Of 1283 clinical samples from female patients based on suspected HPV infection, we found 379 (29%) negatives and 894 (70%) positives. Samples containing >5000 HPV copies/ml were genotyped by sequencing. Of the 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
4
23
1
Order By: Relevance
“…Several studies conducted in European countries, such as Germany, Denmark, and Belgium, on the distribution of HPV types describe type-specific frequencies that agree with our results, with HPV31 being the second most common type, with frequencies of 10.1%, 8.0%, and 7.3%, respectively (1,25,37). The next most common type in our population is HPV58, with a frequency of 6.6%, probably due to the high proportion of women from South America, in which this type is the most frequent after HPV16 (8).…”
Section: Discussionsupporting
confidence: 81%
“…Several studies conducted in European countries, such as Germany, Denmark, and Belgium, on the distribution of HPV types describe type-specific frequencies that agree with our results, with HPV31 being the second most common type, with frequencies of 10.1%, 8.0%, and 7.3%, respectively (1,25,37). The next most common type in our population is HPV58, with a frequency of 6.6%, probably due to the high proportion of women from South America, in which this type is the most frequent after HPV16 (8).…”
Section: Discussionsupporting
confidence: 81%
“…Since the absence of HPV infection means that the risk of cervical cancer is negligible, testing for HPV has now been incorporated into screening programs that previously relied only on cytology (6). HPV DNA analysis has shown encouraging results when used in conjunction with cytological analysis in primary screening for cervical cancer in women 30 years of age or older (5,23). As a result of large randomized clinical trials, testing for HPV DNA is now recommended for most women with equivocal findings on cervical cytological analysis (atypical squamous cells of undetermined significance, also called ASCUS) (1,28).…”
mentioning
confidence: 99%
“…Furthermore, due to the limited number of probes represented by the system and potential cross-hybridizations, it harbours the risk of wrong classifications in a substantial fraction of cases. One study comparing sequencing with hybrid capture identified revealed that about 15% of HPV infections were not found, of which 50% represented HR types [27]. In this study, the hybrid capture technique was not applied.…”
Section: Discussionmentioning
confidence: 93%